Analisis Pengaruh Iklim Organisasi Dan Motivasi Terhadap Kinerja Pegawai Badan Pusat Statistik Provinsi Daerah Istimewa Yogyakarta - Jarwanto, Jarwanto (Universitas Muhammadiyah Yogyakarta, 2014)
The purpose of this research is to look at the effect of organizational climate, the need for achievement, the need for power, and the need for affiliation on the performance of the employees of BPS Special Province of Yogyakarta. The objects of this research are all employees in BPS D.I Yogyakarta totaling 75 people. The data collection was conducted by distributing questionnaires addressed to the employees to obtain an answer for each item of respondents' perception of the variable statement. Of the total questionnaires distributed, 70 questionnaires were returned and readily processed. The data analysis method used was multiple regression analysis to examine the effect of organizational climate, the need for achievement,the need for power, and the need for affiliation on performance.The test conducted partially showed that organizational climate, the need for achievement have a significant positive impact on the performance of the employees of BPS D.I Yogyakarta. On the other hand the need for affiliation and the need for power does not affect the performance of the employees of BPS D.I Yogyakarta. While the test conducted simultaneously showed that organizational climate, the need for achievement, the need for power, and the need for affiliation have a significant positive impact on the performance of the employees of BPS D.I Yogyakarta. The need for achievement has a dominant influence on the performance of the employees of BPS D.I Yogyakarta.Keywords: Organizational Climate, Need Fo Power,Need Fo Achievement,Need For Affiliation, And Performance